2017
DOI: 10.2147/opth.s143886
|View full text |Cite
|
Sign up to set email alerts
|

Phacoemulsification with primary implantation of an intraocular lens in patients with uveitis

Abstract: PurposeTo evaluate the outcome of cataract surgery in adult patients with uveitis.Materials and methodsIn this retrospective cohort study, medical charts of patients with uveitis and matched control patients without uveitis who underwent cataract surgery at the Eye Clinic, Sahlgrenska University Hospital, Mölndal, between January 2005 and December 2009 were analyzed.ResultsThe study included 58 eyes with and 283 eyes without uveitis. The most common etiologies were idiopathic anterior uveitis and Fuchs’ hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 20 publications
6
20
1
1
Order By: Relevance
“…In a metaanalysis, it was suggested that majority of uveitic cataract cases reach normal or near-normal visual acuity after cataract surgery but not as frequent as non-uveitic ager related cataract cases [10]. Several studies have also noted that eyes with well-controlled uveitis had favorable outcomes [3,5,13,40].…”
Section: Intraocular Pressure and Glaucomamentioning
confidence: 99%
See 1 more Smart Citation
“…In a metaanalysis, it was suggested that majority of uveitic cataract cases reach normal or near-normal visual acuity after cataract surgery but not as frequent as non-uveitic ager related cataract cases [10]. Several studies have also noted that eyes with well-controlled uveitis had favorable outcomes [3,5,13,40].…”
Section: Intraocular Pressure and Glaucomamentioning
confidence: 99%
“…One of the most frequent complications that occur in patients with uveitis is cataract formation. Cataract may arise due to the inflammation itself or as a result of corticosteroid treatments [3].…”
Section: Introductionmentioning
confidence: 99%
“…After surgery, transient rising of intraocular pressure was noticed in 4 eyes (10,81%) more frequent than in non-uveitis patients, estimated at 0,5% [ 2 ]. Prolonged postoperative inflammation (more than 14 days) was present in 3 eyes.…”
Section: Resultsmentioning
confidence: 99%
“…Surgical management of complicated cataract after anterior uveitis needs additional actions, especially for achieving and maintaining a good mydriasis [ 4 ] or for a good stabilization of the intraocular lens. Posterior capsule opacification is the most frequent issue in these patients [ 2 , 5 ]. Cystoid macular edema occurs after surgery in the patients who suffered posterior capsule rupture (accidentally or by Nd-YAG laser capsulotomy); some authors state that perioperative systemic therapy is protective against those complications [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation